A Comprehensive Assessment of Psychosocial Well-being Among Growing Rod Graduates: A Preliminary Investigation. Issue 2 (1st February 2023) - Yildiz, Mevhibe İrem; Goker, Barlas; Demirsöz, Talat; Aslan, Cihan; Demirkiran, Halil Gokhan; Karahan, Sevilay; Yazici, Mumin Kazim; Yazici, Müharrem
Abstract : Background: Traditional growing rods (TGR) encompass a long process, in which patients experience physical and psychosocial difficulties. However, the effect of repeating surgeries on the overall psychological functioning of graduated patients has not been thoroughly investigated in the literature. The aim of this study is to evaluate the psychological well-being of graduated idiopathic early-onset scoliosis patients in terms of psychopathology, neurocognition, and psychosocial functioning, and determine the accuracy of scoliosis outcome questionnaires in these regards. Methods: TGR graduates with idiopathic early-onset scoliosis without known intellectual disabilities or neuromuscular impairments were included. Patients were thoroughly evaluated using psychological instruments [Wechsler Adult Intelligence Scale, Auditory Consonant Trigram Test, Verbal Fluency Test, Beck Depression Inventory, Beck Anxiety Inventory, Rosenberg Self-Esteem Scale, Symptom Checklist-90, Post-Traumatic Growth Inventory, Strengths and Difficulties Questionnaire, Spinal Appearance Questionnaire, Scoliosis Research Society 22-item questionnaire (SRS-22)]. Results were compared with normative data when available. Spearman correlations were performed between the results of these tests, the total treatment duration, and the number of spinal surgeries. Results: Of the 15 patients included in the study, 9 were females, and the mean age was 18.73 (16 to 23). The mean age at index surgery was 6.38 (3 to 10) whereas that of graduation was 14.00 (12 to 16). The average number of spinal surgeries was 14.28 (7 to 20). Two patients performed below the range of adult intellectual functioning. Auditory Consonant Trigram Test showed normal verbal working memory and attention control. Six patients had abnormal Verbal Fluency Test performance. Eight patients had abnormal ratings on at least one of the assessment scales of psychopathology (Symptom Checklist-90, Beck Depression Inventory, and Beck Anxiety Inventory). Eight patients had low-to-moderate self-esteem (Rosenberg self-esteem scale). The median spinal appearance questionnaire and SRS-22 scores were 34 and 4.18, respectively. Pain and function subdomains of SRS-22 scored higher than self-image and mental health. No correlation was found between the treatment duration and number of surgeries and test scores. SRS-22 showed correlations with multiple psychological tests. Conclusion: Completed TGR treatment yields acceptable correction of deformities and surgical outcomes, however, may fail to improve psychological well-being. This is the first study to find various psychosocial abnormalities in two-thirds of cases. Level of Evidence: Level IV; cross-sectional study.